2019
DOI: 10.1590/2175-8239-jbn-2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

Cecum perforation associated with a calcium polystyrene sulfonate bezoar - a rare entity

Abstract: Hyperkalemia is one of the most common electrolyte disorders, responsible for a high number of adverse outcomes, including life-threatening arrhythmias. Potassium binders are largely prescribed drugs used for hyperkalemia treatment but unfortunately, there are many adverse events associated with its use, mostly gastrointestinal. Identification of patients at highest risk for the serious complications associated with the current potassium binders, such as colon necrosis and perforation, could prevent fatal outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This leaves clinicians to weigh the risks and benefits of its use on a case by case basis (22). Initially, gastrointestinal mucosal injury was attributed to the sorbitol, which is commonly used in solution with the SPS; however, subsequent investigations showed that the resin itself is capable of causing injury as well (24,27,28).…”
Section: Case Presentationmentioning
confidence: 99%
“…This leaves clinicians to weigh the risks and benefits of its use on a case by case basis (22). Initially, gastrointestinal mucosal injury was attributed to the sorbitol, which is commonly used in solution with the SPS; however, subsequent investigations showed that the resin itself is capable of causing injury as well (24,27,28).…”
Section: Case Presentationmentioning
confidence: 99%
“…Patients may be asymptomatic or present with a spectrum of gastrointestinal symptoms, ranging from mild symptoms such as pain, nausea, and/or anorexia to more severe symptoms such as perforation or obstruction from mass effect or intussusception [2][3][4][5][6][7][8]. Early diagnosis and treatment of bezoars are therefore vital, with the management approach largely dependent on the type of material ingested.…”
Section: Introductionmentioning
confidence: 99%
“…The location of the impaction varies as well, with the majority in the stomach, followed by the duodenum and the esophagus [2]. Patients may be asymptomatic or present with a spectrum of gastrointestinal symptoms, ranging from mild symptoms such as pain, nausea, and/or anorexia to more severe symptoms such as perforation or obstruction from mass effect or intussusception [2][3][4][5][6][7][8]. Early diagnosis and treatment of bezoars are therefore vital, with the management approach largely dependent on the type of material ingested.…”
Section: Introductionmentioning
confidence: 99%